A national census of ambulance response times to emergency calls in Ireland. Issue 6 (1st November 2000) - Breen, Nick; Woods, Julie; Bury, Gerard; Murphy, Andrew W; Brazier, Hugh
Abstract : Background —Equity of access to appropriate pre-hospital emergency care is a core principle underlying an effective ambulance service. Care must be provided within a timeframe in which it is likely to be effective. A national census of response times to emergency and urgent calls in statutory ambulance services in Ireland was undertaken to assess current service provision. Methods —A prospective census of response times to all emergency and urgent calls was carried out in the nine ambulance services in the country over a period of one week. The times for call receipt, activation, arrival at and departure from scene and arrival at hospital were analysed. Crew type, location of call and distance from ambulance base were detailed. The type of incident leading to the call was recorded but no further clinical information was gathered. Results —2426 emergency calls were received by the services during the week. Fourteen per cent took five minutes or longer to activate (range 5–33%). Thirty eight per cent of emergencies received a response within nine minutes (range 10–47%). Only 4.5% of emergency calls originating greater than five miles from an ambulance station were responded to within nine minutes (range 0–10%). Median patient care times for "on call" crews were three times longer than "on duty" crews. Conclusion —Without prioritised use of available resources, inappropriately delayed responses to critical incidents will continue. Recommendations are made to improve the effectiveness of emergency medical service utilisation.